Dimethylsulfoniopropionate (DMSP), dimethylsulfoxide (DMSO) and dimethylsulfide (DMS) concentrations were measured in the yellow Sea and Bohai Sea during the spring (2014.5), summer (2015.8), autumn (2014.11) and winter (2016.1) - Mao, Shi-Hai; Zhuang, Guang-Chao; Liu, Xin-Wei; Jin, Na; Zhang, Hong-Hai; Montgomery, Andrew; Liu, Xi-Ting; Yang, Gui-Peng (PANGAEA, 2020)
We conducted the first measurements of dimethylsulfoniopropionate (DMSP), dimethylsulfoxide (DMSO) and dimethylsulfide (DMS) over four consecutive seasons across a wide range of study sites in anthropogenically impacted marginal seas of north China (Bohai sea and Yellow sea). We also determined the biological production and consumption rates of DMS at selected sites during spring (2014.5), summer (2015.8), autumn (2014.11) and the distributions of Chl-a, DMS, DMSP, and DMSO in the sea surface microlayer during autumn.
Keywords: Bohai Sea; Dimethylsulfide (DMS); Dimethylsulfoniopropionate (DMSP); Dimethylsulfoxide (DMSO); Yellow Sea